SISTEM MONITORING PENGGUNAAN DAYA LISTRIK BERBASIS IOT STUDI KASUS PEMBAGIAN TAGIHAN LISTRIK PENGHUNI KOST - Indra Maulana Yusup Kusumah; Yus Jayusman; Muhammad Rijalul Hakim (LPPM STMIK Bandung, 2023)
Electrical energy has become one of the main needs in this modern era. Along with the development of technology, now people's activities have begun to use a lot of electronic devices which basically require electrical energy as a resource. Without realizing it, the more use of electronic devices, the greater the electricity bill that must be paid each month. The use of electricity in a boarding house often causes jealousy among the residents. Usually the boarding house owner is charged the same electricity bill by the boarding owner while the electricity usage is different. The main problem faced is the absence of a system that can read the electricity usage of each occupant of the boarding house. This makes boarding house owners unable to share electricity bills proportionally between those who are frugal and those who are wasteful. The monitoring system for electricity usage will help boarding house owners to be able to limit and share electricity bills proportionally among the occupants. This system is designed using the IoT concept with the ESP8266 module and the PZEM-004T sensor as a measuring tool. This system reads the occupants' electricity usage from time to time and the data is stored on a data server. Information can be accessed through a website that can present the results of the use of electric power by the occupants of the boarding house in the form of usage graphs along with the amount of electricity bills for each room in the boarding house.